Republic of Kazakhstan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper presents an assessment of leveraging oil wealth for development in Kazakhstan. By saving most of the tax revenues collected from the oil sector in an off-budget oil fund Kazakhstan has been relatively successful in ensuring that government revenue volatility does not translate into spending volatility. The quasifiscal sector, that includes public enterprises in the oil and gas industry, is systemic in Kazakhstan. During the crisis the quasifiscal sector played an important role in the government's stimulus program while currently it is actively involved in the country's long- term development strategy.